Understanding day care enrolment gaps - Jonas Jessen; Sophia Schmitz; Sevrin Waights (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We document day care enrolment gaps by family background for children under 3 in Germany. Research demonstrates that children of less-educated or foreign-born parents benefit most from day care, making it important to understand the causes of such enrolment gaps. Using a unique data set that records both actual and preferred day care usage, we demonstrate that differences in demand cannot fully explain the enrolment gaps. Investigating supply-side factors using quasi-experimental designs, we find that reducing both parental fees and scarcity of places significantly decreases enrolment gaps by parental education but not by parental country of birth. We discuss implications.
Keywords: I24; J13; 330; Child care; Early education; Inequality; Socio-economic status; Discrimination; Synthetic control